NILAI-NILAI TASAWWUF DALAM FIKIH MU'AMALAH - Jonwari Jonwari (LP2M Universitas Ibrahimy, 2017)
Application concept in fiqh-tasawwuf that level of social reality. There is a serious controversian between fiqh and tasawwuf at stage of practitioner. Not infrequently, fiqh doctrine is always clashing with teachings of tasawwuf. From the assumption that fiqh is consider nuance legal-formal, rather than tasawwuf which is ethical value. Therefore, the law is binding and forcing while tasawwuf flexible. Then, that make fiqih rigid, stiff and inflexible. So often, fiqih does not seem to care about wishes of tasawwuf. On the contrary, at a further stage, some people who have reached the top of tasawwuf, feel unnecessary to formal rules of fiqh.